Human Wharton’s Jelly Mesenchymal Stem Cells and their Extracellular Vesicles in the Management of Bleomycin-induced Lung Injury in Model Animals: A Comparative Preclinical Study Focused on Histomorphometric Analysis - Krishnan, Anand; Vijayakumar Sreelatha, Harikrishnan; Arumugam, Sabareeswaran; Kasoju, Naresh (Current Stem Cell Research & Therapy, 2025)
IntroductionPulmonary fibrosis, a condition characterized by excessive lung tissue scarring, remains a significant therapeutic challenge. Given the potential of human Wharton’s jelly-derived mesenchymal stem cells (hWJ-MSCs) and their small extracellular vesicles (hWJ-MSC-EVs) as minimally invasive and scalable therapeutic options for pulmonary fibrosis in clinical settings, this study investigates the potential of hWJ-MSCs and hWJ-MSC-EVs in mitigating bleomycin-induced lung injury in C57BL/6J mice.MethodshWJ-MSCs were cultured and characterized for their ability to differentiate into osteogenic, adipogenic, and chondrogenic lineages. EVs were successfully induced via serum starvation, purified using ultracentrifugation, and characterized for their protein and nucleic acid content, size distribution, and EV markers. A bleomycin-induced pulmonary fibrosis model was established in C57BL/6J mice. Mice were monitored for weight loss, mortality, and lung fibrosis severity following treatment with hWJ-MSCs and hWJ-MSC-EVs. Histological analysis and Ashcroft scoring were used to assess lung fibrosis.ResultsBleomycin administration in mice resulted in significant weight loss, increased mortality, and severe lung fibrosis, as demonstrated by histological analysis and Ashcroft scoring. Treatment with hWJ-MSCs and hWJ-MSC-EVs significantly alleviated these symptoms. Mice receiving these treatments exhibited improved body weight, enhanced survival rates, and reduced lung fibrosis, with notable improvements in alveolar structure and decreased fibrotic tissue deposition.ConclusionThese findings highlight the potential of hWJ-MSCs and hWJ-MSC-EVs as therapeutic agents in treating pulmonary fibrosis by reducing inflammation and promoting lung tissue repair, offering a potential new avenue for regenerative therapy in severe lung diseases. Future research directions involve elucidating the molecular pathways involved in tissue repair, optimizing therapeutic delivery, and conducting comprehensive clinical evaluations.
Keywords: Human wharton’s jelly